Hepatitis C virus-induced natural killer cell proliferation involves monocyte-derived cells and the OX40/OX40L axis - Pollmann, Julia; Rupp, Daniel; Grünvogel, Oliver; Mutz, Pascal; Lasitschka, Felix; Lohmann, Volker; Bartenschlager, Ralf; Cerwenka, Adelheid (Journal of hepatology, 2018)
Background & Aims Natural killer (NK) cells are found at increased frequencies in patients with hepatitis C virus (HCV). NK cell activation has been shown to correlate with HCV clearance and to predict a favourable treatment response. The aim of our study was to dissect mechanisms leading to NK cell activation and proliferation in response to HCV. Methods: NK cell phenotype, proliferation, and function were assessed after the 6-day co-culture of human peripheral blood mononuclear cells with either HCV replicon-containing HuH6 hepatoblastoma cells or HCV-infected HuH7.5 cells. The results obtained were confirmed by immunohistochemistry of liver biopsies from patients with HCV and from HCV-negative controls. Results: In HCV-containing co-cultures, a higher frequency of NK cells upregulated the expression of the high-affinity IL-2 receptor chain CD25, proliferated more rapidly, and produced higher amounts of interferon γ compared with NK cells from control co-cultures. This NK cell activation was dependent on IL-2, cell-cell contact-mediated signals, and HCV replicon-exposed monocytes. The tumour necrosis factor-receptor superfamily member OX40 was induced on the activated CD25± NK cell subset and this induction was abrogated by the depletion of CD14+ monocytes. Moreover, OX40L was upregulated on CD14± monocyte-derived cells co-cultured with HCV-containing cells and also observed in liver biopsies from patients with HCV. Importantly, blocking of the OX40/OX40L interaction abolished both NK cell activation and proliferation. Conclusions: Our results uncover a previously unappreciated cell-cell contact-mediated mechanism of NK cell activation and proliferation in response to HCV, mediated by monocyte-derived cells and the OX40/OX40L axis. These results reveal a novel mode of crosstalk between innate immune cells during viral infection. Lay summary: Using a cell-culture model of hepatitis C virus (HCV) infection, our study revealed that natural killer (NK) cells become activated and proliferate when they are co-cultured with HCV-containing liver cells. The mechanism of this activation involves crosstalk with other innate immune cells and a cell-cell contact interaction mediated by the cell surface molecules OX40 and OX40L. Our study reveals a novel pathway leading to NK cell proliferation and activation against virus-infected cells that might be of relevance in antiviral immunity.